Prevalence and progression of P-wave abnormalities in patients with atrial fibrillation - Relander, Arto; Kääriä, Johanna; Jaakkola, Samuli; Vasankari, Tuija; Nuotio, Ilpo; Airaksinen, Juhani K. E.; Kiviniemi, Tuomas (Elsevier BV, 2026)
Background
Various electrocardiographic P-wave indices are associated with cardiovascular comorbidities, such as atrial fibrillation (AF) and stroke. However, information on their stability is limited.
Objective
This study explored the prevalence and progression of P-wave abnormalities (PWAs) as well as their risk factors in an AF population.
Methods
PWAs were identified in a series of 3 sinus rhythm electrocardiograms (ECGs) of 1316 individuals undergoing the index cardioversion (CV) for acute AF in the FinCV study. Patients were assigned to the category of extensive PWA if they had P-wave duration ≥180 ms, P-terminal force ≥80 mm·ms, advanced interatrial block (biphasic P waves in inferior leads and P-wave duration ≥120 ms), or deflected P-wave morphology; moderate PWA consisted of P-wave duration of 150–180 ms or P-terminal force of 40–80 mm·ms.
Results
Between pre-CV and index CV ECGs, 133 of 342 (38.9%) and 54 of 342 (15.8%) patients progressed from normal P wave to moderate and extensive PWAs, respectively. During the follow-up after index CV, the respective rates were 131 of 407 (32.2%) and 74 of 407 (18.2%). At the end of follow-up, prevalence for normal P wave was 311 of 1121 (27.7%), whereas 434 (38.7%) patients had moderate PWA and 376 (33.5%) had extensive PWA. Increasing age, heart failure, hypertension, vascular disease, history of previous AF episodes, high CV frequency, left ventricular hypertrophy, and wide QRS complex in the ECG were independent risk factors for persistent or progressive PWA status in a Cox regression analysis.
Conclusion
The prevalence and rate of progression of PWA are high in this cohort of AF patients, with development mainly driven by aging, chronic cardiovascular conditions, and frequent AF recurrences.